The Impact of Developing Hispanic-Serving Institution Program on College Persistence, Completion Rates, and Student Debt - Li Feng; Yao-Yu Chih; Yunwei Gai; Lynn MacDonald (CESifo GmbH, 2024)
The Developing Hispanic-Serving Institution (DHSI) Program is one of the largest federal grant programs that support Hispanic-Serving Institutions. We employ an eleven-year panel dataset of U.S. higher education institutions to implement a difference-in-differences (DID) design, two-way fixed effect model (TWFE), and propensity score matching (PSM) to compare DHSI grantee institutions with other Title V eligible higher education institutions that did not receive DHSI funding. We find that the receipt of DHSI grant funding helps these institutions significantly improve their retention rates (2~ percentage points), completion rates (1-3 percentage points), and reduce their students' debt level (e.g., 500~1000 lower for graduated students). Our back-of-the-envelope cost-benefit calculation shows that the DHSI program benefits exceed cost.
Keywords: H52; I22; I23; I28; 330; Developing Hispanic-Serving Institution (DHSI) Program; Hispanic-Serving Institutions (HIS); difference-in-differences (DID) design; two-way fixed effect model (TWFE); propensity score matching (PSM) approach